Periodontitis and cardiometabolic disorders: The role of lipopolysaccharide and endotoxemia - Pussinen, Pirkko J.; Kopra, Elisa; Pietiäinen, Milla; Lehto, Markku; Zaric, Svetislav; Paju, Susanna; Salminen, Aino (Periodontology 2000, 2022)
Lipopolysaccharide is a virulence factor of gram‐negative bacteria with a crucial importance to the bacterial surface integrity. From the host's perspective, lipopolysaccharide plays a role in both local and systemic inflammation, activates both innate and adaptive immunity, and can trigger inflammation either directly (as a microbe‐associated molecular pattern) or indirectly (by inducing the generation of nonmicrobial, danger‐associated molecular patterns). Translocation of lipopolysaccharide into the circulation causes endotoxemia, which is typically measured as the biological activity of lipopolysaccharide to induce coagulation of an aqueous extract of blood cells of the assay. Apparently healthy subjects have a low circulating lipopolysaccharide activity, since it is neutralized and cleared rapidly. However, chronic endotoxemia is involved in the pathogenesis of many inflammation‐driven conditions, especially cardiometabolic disorders. These include atherosclerotic cardiovascular diseases, obesity, liver diseases, diabetes, and metabolic syndrome, where endotoxemia has been recognized as a risk factor. The main source of endotoxemia is thought to be the gut microbiota. However, the oral dysbiosis in periodontitis, which is typically enriched with gram‐negative bacterial species, may also contribute to endotoxemia. As endotoxemia is associated with an increased risk of cardiometabolic disorders, lipopolysaccharide could be considered as a molecular link between periodontal microbiota and cardiometabolic diseases.